Identifying Efficiency of Banks’ Performance Using Financial Indicators in Bangladesh During the COVID-19 Pandemic: Analysis of Slack-Based DEA Approach - Kundu, Nobinkhor; Tara, Mst. Noiyan; Mahbub, Gazi Mohammed (International Finance and Banking, 2024)
The purpose of this study is to examine slack-based data envelopment analysis (DEA) to determine the efficiency of commercial bank performance in Bangladesh at post-Basel III in the COVID-19 pandemic. The secondary data was gathered from several annual reports of forty-three commercial banks in Bangladesh for the year 2020. This study found that thirteen DMUs indicating that "perfectly efficient" financial ratios. Moreover, six DMUs obtained efficiency scores of 90 percent to 99 percent, and nine DMUs obtained efficiency scores of 80 percent to 89 percent, which indicates that they have a "highly efficient" financial ratio. The bank efficiency score ranges from 60 percent to 79 percent, which indicates that fifteen DMUs have "moderately efficient" financial ratios. Thus, DMU2 is the most efficient, which indicates "perfectly efficient" financial ratios, and DMU6 is the least efficient, which indicates "moderately efficient" financial ratios amongst the selected forty-three commercial banks in Bangladesh.